Legal Aspects of the Machinery Import Duty Exemption Facility Policy: An Analysis of the Impact on Industry in Indonesia - Amanda Junaedi (SEAN Institute, 2025)
The granting of import duty exemption facilities on imported machinery for industry is one form of facility in the field of taxation provided by the government for new investors who intend to invest or open new industries in Indonesia. Through this research the author wants to know what is the background of the Indonesian government in granting the facility, how is the system of granting this machine import duty exemption facility and how is the legal responsibility of receiving the machine import duty exemption facility for industry in Indonesia. The research method used is normative juridical, this research focuses on the study of applicable laws and regulations, legal theories, legal concepts, and legal principles relevant to the research topic. In other words, researchers will deeply analyze the legal rules governing import duty exemptions for industry, and try to understand the implications of these rules. This research is expected to contribute to further understanding of government policies in encouraging investment in the industrial sector. In addition, the results of this study can also be expected to be taken into consideration for business actors in utilizing the import duty exemption facility.